Phylogenetic relationships within the New World subfamily Larreoideae (Zygophyllaceae) confirm polyphyly of the disjunct genus Bulnesia. Issue 5 (4th July 2018) - Godoy-Bürki, A. C.; Acosta, J. M.; Aagesen, L.
Abstract : The Larreoideae subfamily is the major representative of the family Zygophyllaceae in South America, where several of its members are common to dominant in arid regions of the Southern Cone. However, there are currently no phylogenetic analyses of the subfamily that may help to understand its origin and diversification. Additionally, there are taxonomic discrepancies around Bulnesia Gay (1845), one of its more important genera. Accordingly, we performed a phylogenetic analysis combining chloroplast ( rbcL and trnL-F ) and nuclear (ITS) DNA sequences. Bayesian and Parsimony analyses were performed to highlight the intergeneric relationships within Larreoideae. All genera with the exception of Bulnesia are monophyletic and we propose to redefine Bulnesia, dividing it in two genera. Furthermore, other taxonomic issues of the remaining genera are solved. This study represents the first approximation to clarify the phylogenetic relationships amongst all Larreoideae genera, producing a phylogenetic framework that can be used in future macro-ecological studies.